Functional Dissection of a Poliovirus cis-Acting Replication Element [PV-cre(2C)]: Analysis of Single- and Dual-cre Viral Genomes and Proteins That Bind Specifically to PV-cre RNA - Yin, Jiang (American Society for Microbiology, 2003)
The role of the cis replication element (cre) in the 2C(ATPase) coding region of the poliovirus (PV) genome has been studied with a series of mutants derived from either a PV1 full-length genome or a replicon (P/L) containing the firefly luciferase reporter gene in place of the capsid region. Using the P/L replicon we have inserted cre elements at three different locations in the genome including the 5′ nontranslated region and within the open reading frame. The successful recovery of replication of a nonviable P/L (A(5)C) mutant replicon with an artificial cre element as “rescuer,” in addition to the results of site-directed mutagenesis and experiments with truncated forms of PV-cre(2C), indicated that (i) the sequence within the upper stem and loop regions contains the minimal cre RNA required for VPg uridylylation in vitro, (ii) the location of the cre RNA in the poliovirus genome is not relevant to RNA infectivity, and (iii) specific binding of 3CD(pro) to PV-cre(2C) occurs within the upper stem region and probably involves several contact residues. The role of a 14-nucleotide conserved “core” sequence among known cre structures in picornaviruses was examined by site-directed mutagenesis of individual nucleotides. In addition to a conserved AAA (4472 to 4474) triplet previously shown to be the primary RNA template for VPg uridylylation by the PV RNA polymerase 3D(pol) (E. Rieder, A. V. Paul, D. W. Kim, J. H. van Boom, and E. Wimmer, J. Virol. 74:10371-10380, 2000), we have now shown that important residues (G(4468) and A(4481)) are contained in a predicted internal bulge at the upper stem-loop of PV-cre(2C). We have further demonstrated that the viral proteins 3CD(pro) and 3C(pro) form stable complexes with a transcript PV-cre(2C) RNA that can be considered critical for VPg uridylylation.